2010
DOI: 10.1057/jphp.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in prisons: The need for effective and acceptable interventions

Abstract: Tobacco-smoking prevalence has been decreasing in many high-income countries, but not in prison. We provide a summary of recent data on smoking in prison (United States, Australia, and Europe), and discuss examples of implemented policies for responding to environmental tobacco smoke (ETS), their health, humanitarian, and ethical aspects. We gathered data through a systematic literature review, and added the authors' ongoing experience in the implementation of smoking policies outside and inside prisons in Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 31 publications
1
29
1
3
Order By: Relevance
“…These results are comparable to previous published studies (Fazel et al, 2006;Hoffmann, 2002;Ritter et al, 2011). A report collecting data of drug use among prisoners in the European Union indicated that one-third of prisoners show problematic drug-use patterns (EMCDDA, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are comparable to previous published studies (Fazel et al, 2006;Hoffmann, 2002;Ritter et al, 2011). A report collecting data of drug use among prisoners in the European Union indicated that one-third of prisoners show problematic drug-use patterns (EMCDDA, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…In prisons, the scenario is similar. Previous studies which were carried out in United States of America (USA), Australia and Europe found a smoking prevalence of 64 to 91.8% amongst inmates, which corresponds to a number three times higher than the general population (Ritter, Stover, Levy, Etter, & Elger, 2011).…”
mentioning
confidence: 82%
“…So werden für männliche Gefangene in der Schweiz 79%, in Großbri-tannien 80%, in Litauen 86%, in Polen 81%, in Griechenland 92% und in Frankreich 98% berichtet. Auf ähnlich hohem Niveau liegen die entsprechenden Anteile der Frauen: 95% in Kanada, 99% in Großbritannien, 82% in Litauen und 59% in der Schweiz (Ritter, Stöver et al 2011). …”
Section: Inhaltsverzeichnisunclassified
“…In prison A, the SHS intervention consisted of an extension of smoke-free zones: in 2009, smoking was allowed everywhere except at some indoor workplaces. From 2010 onwards, smoking was allowed only in cells and outdoors (Ritter et al, 2011). In prisons B and C in 2009, prisoners were allowed to smoke only in cells, during their outdoor exercise and in one smoking room in prison C, but these rules were loosely enforced and respected.…”
Section: Interventionsmentioning
confidence: 99%
“…The high smoking prevalence in prisons results in exposure to second-hand smoke (SHS), a recognized carcinogen (Boffetta et al, 1998). Concentrations of SHS may be very high in prison cells (Hammond and Emmons, 2005;Proescholdbell et al, 2008;Ritter et al, 2011) and overcrowding increases this problem, as it results in higher concentrations of smoke. In addition, because of the wide availability of tobacco and the social pressure to smoke in prisons, some nonsmoking inmates may start to smoke or relapse to smoking (Belcher et al, 2006;Cropsey et al, 2008;Papadodima et al, 2009).…”
Section: Introductionmentioning
confidence: 99%